2010
DOI: 10.1016/j.ejvs.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin and Rifampin Alone and in Combination Prevent Vascular Graft Biofilm Formation and Emergence of Antibiotic Resistance in a Subcutaneous Rat Pouch Model of Staphylococcal Infection

Abstract: Daptomycin is an important candidate for prevention of staphylococcal biofilm-related infection and rifampin could serve as an interesting anti-staphylococcal antibiotic enhancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 32 publications
2
44
1
1
Order By: Relevance
“…Unlike other studies 8,12,13 , we demonstrated that rifampicin alone is worse than vancomycin for inhibiting staphylococci embedded in biofilm. On the other hand, rifampicin in combination with vancomycin at 15mg/l inhibited bacterial grown in biofilm and, therefore, improved vancomycin activity, because of rifampicin's better biofilm penetration 10,20 .…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Unlike other studies 8,12,13 , we demonstrated that rifampicin alone is worse than vancomycin for inhibiting staphylococci embedded in biofilm. On the other hand, rifampicin in combination with vancomycin at 15mg/l inhibited bacterial grown in biofilm and, therefore, improved vancomycin activity, because of rifampicin's better biofilm penetration 10,20 .…”
Section: Discussioncontrasting
confidence: 44%
“…Otherwise, in our setting, vancomycin is preferable as antimicrobial coverage, and rifampicin is unusually prescribed. Because studies have demonstrated that rifampicin in combination with other drugs might be more effective 12,13 despite contradictory results 15 , we decided to investigate rifampicin activity alone and in combination with vancomycin against biofilm-forming MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of DPT with rifampin appears useful for treating biofilm, as a consequence of a synergistic mechanism, as showed by Cirioni et al [36] Indeed, authors found that the combination of these molecules had higher efficacy than that of each single compound for treating a rat model of Staphylococcal infection. Authors suggest that the positive interaction between DPT and rifampin could be explained by the mechanism of action of DPT, which opens channels in the cell membrane, promoting entry of hydrophobic drugs such as rifampin.…”
Section: Daptomycin Lock Therapymentioning
confidence: 84%
“…As is the case for many antibiotics, daptomycin has been shown to exhibit a significant bactericidal activity against planktonic cells (7)(8)(9). However, the eradication of adherent bacteria is rarely achieved despite the large number of in vitro and animal studies in which daptomycin activity was evaluated (10)(11)(12)(13)(14)(15)(16). Besides the results of the literature that appear controversial (17), direct comparison between studies is not directly possible, since the biofilm growth and treatment protocols used differ greatly.…”
mentioning
confidence: 93%